How-to-Guide Note for the World Bank Technical Assistance to Burundi for the Adoption of a Semi-automatic Pricing Mechanism in the Petroleum Sector - World Bank (Washington, DC, 2013)
In May 2008, the government of Burundi requested Bank assistance to review the situation of the petroleum market, and evaluate the existing pricing mechanism. Following three Bank missions, a draft report was prepared and submitted to the Burundian authorities. Both the Ministry of Commerce and the Ministry of Finance submitted comments on the draft report. The draft and the government s comments were discussed with a Bank economic mission in April 2009. The present note is focused on the petroleum pricing issue and takes into account the comments of the government and the conclusions of the discussions with the Bank mission in April. Following an analysis of the petroleum supply chain, the report presents the main conclusions and recommendations of the Bank s petroleum expert on the current pricing mechanism; summarizes the views of the authorities on recent changes in their management of domestic prices; and describes the new measures the government plans to take to consolidate the existing quasi-automatic price adjustment mechanism and to stabilize the market supply and the specific cost components. The report also discusses briefly how the social impact of price increases is already taken care of in the current pricing mechanism.